Supported copper-based catalyst for high-temperature synthesis of methanol as well as preparation method and application of supported copper-based catalyst

By using high-energy plasma sputtering method to support copper nanoparticles on the oxide support, a supported copper-based catalyst was solved, and the conversion rate and selectivity of existing copper-based catalysts cannot be achieved both in the reaction of CO2 hydrogenation to methanol at high temperatures was achieved, and an efficient methanol yield was achieved.

CN119838602AActive Publication Date: 2025-04-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311347271.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

In the existing copper-based catalysts used in the hydrogenation of CO2 at high temperatures to methanol, there is a "seesaw effect" in the conversion rate and methanol selectivity, and it is difficult to obtain a higher methanol yield.

Method used

The copper nanoparticles were loaded on an oxide support containing zinc and zirconium components by high-energy plasma sputtering method to form a supported copper-based catalyst. The metal-support strong interaction interface was formed through reduction treatment, which promoted the hydrogenation conversion of formate intermediate species and the desorption of methanol products.

Benefits of technology

Under high temperature conditions, the supported copper-based catalyst significantly improves CO2 conversion and methanol selectivity, improves methanol yield, and solves the problem that existing catalysts cannot have both selectivity and conversion rates at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838602A_ABST
    Figure CN119838602A_ABST
Patent Text Reader

Abstract

The invention discloses a supported copper-based catalyst for high-temperature synthesis of methanol as well as a preparation method and application of the supported copper-based catalyst, and belongs to the technical field of catalyst preparation and application. According to the catalyst, copper serves as a main active component, an oxide containing zinc and zirconium serves as a carrier, copper nanoparticles are loaded on the carrier in one step through a high-energy plasma sputtering method, and the catalyst can be applied to the reaction for preparing methanol through carbon dioxide hydrogenation under the condition of high reaction temperature. Compared with a commercially used Cu / ZnO / Al2O3 catalyst, under the reaction condition of 300 DEG C, the selectivity of methanol is improved to 85% from 10%, and the space time yield of methanol is improved by 2.6 times. The method is beneficial to exploiting a new field of synthesizing methanol by using a copper-based catalyst at a relatively high reaction temperature, on one hand, the problem that a noble metal catalyst or an oxide catalyst is easy to generate a methane or carbon monoxide byproduct is solved, and on the other hand, the seesaw limitation that the conversion rate of carbon dioxide and the selectivity of methanol cannot be obtained at the same time is broken through; good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst preparation and application, and specifically relates to a supported copper-based catalyst prepared by a sputtering method and its application in a high-yield methanol product obtained by a carbon dioxide hydrogenation reaction under high temperature conditions. Background Art

[0002] The greenhouse effect caused by carbon emissions has brought about a series of environmental crises, such as ocean acidification, global warming, and sea level rise, posing a huge threat to human survival. Under the background of carbon neutrality and carbon peak, methanol, as an important hydrogen storage medium, can store hydrogen obtained from renewable energy into organic liquid methanol through CO2 molecules, which is conducive to the storage and transportation of hydrogen energy. In addition, methanol is an important C1 platform compound that can be further converted into important basic raw materials such as low-carbon olefins and aromatics. By connecting the CO2 hydrogenation reaction catalyst and the molecular sieve catalyst in series, CO2 can be converted into a variety of fuels and high-value chemicals with methanol as an intermediate. The CO2 hydrogenation to methanol reaction is of great significance for controlling greenhouse gases and replacing fossil fuels.

[0003] Although the synthesis gas to methanol process has achieved commercial industrial production after nearly a hundred years of development, the CO2 molecule is relatively stable and is not conducive to the activation of CO2 at low temperatures. The activity of CO2 hydrogenation reaction is generally low, and it is limited by the reaction temperature of the molecular sieve catalyst. This route needs to be carried out at a higher temperature (300-400°C). However, the CO2 hydrogenation reaction is an exothermic reaction, and low temperature is conducive to the formation of methanol. Although the CO2 conversion rate increases at high temperatures, a large amount of CO by-products will be produced, resulting in a low selectivity of the target product methanol. Therefore, due to the dual limitations of thermodynamics and CO2 chemical inertness, there is a "seesaw effect" between the conversion rate of CO2 and the selectivity of methanol on the commonly used Cu catalyst, and it is difficult to obtain a high methanol yield. Therefore, it is very important to develop a CO2 hydrogenation to methanol catalyst that can be used at higher temperatures.

[0004] Commonly used CO2 hydrogenation to methanol catalysts include copper-based catalysts, precious metal catalysts, and oxide catalysts. The Chinese invention patent with application number 202111545432.7 discloses a metal-doped Cu-Zn-Zr / SiC catalyst. Under the conditions of 6MPa, 230°C, and 6000mL / (h·g), the aluminum-doped catalyst has the best performance, with a carbon dioxide conversion rate of 26.8% and a methanol selectivity of 81.8%. However, the reaction conditions required for this catalyst are relatively harsh, and it only has a high methanol selectivity at low temperatures and cannot be used at high temperatures. The Chinese invention patent with application number 201710756830.0 discloses a ZnZrOx solid solution oxide catalyst for the synthesis of methanol from carbon dioxide hydrogenation. The solid solution catalyst has a high selectivity for methanol at 5MPa, 320°C, and 24000h -1 Under the following conditions, methanol selectivity can exceed 88% at high temperature, and the single-pass conversion rate of carbon dioxide is 10%, but the reaction conditions are relatively harsh. The Chinese invention patent with application number 202210822628.4 discloses a CuGaZrOx catalyst for synthesizing methanol by hydrogenation of carbon dioxide. Although the methanol selectivity can be stabilized at 88-89% under the conditions of 3MPa, 280°C, and 6000mL / (h·g), the single-pass conversion rate of carbon dioxide is only 5.4-6.6%, and the methanol selectivity drops sharply after the reaction temperature is higher than 300°C. In addition, although the catalyst contains Cu components, Cu atoms are doped in the ZrO2 lattice, and are doping additives like Ga atoms. They are essentially ZrO2-based oxide catalysts, not Cu-based supported catalysts with Cu as the active component. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a supported copper-based catalyst for high-temperature synthesis of methanol and its preparation method and application. The present invention solves the technical problem that the conversion rate and methanol selectivity of the existing copper-based catalyst in the reaction of CO2 hydrogenation to methanol at high temperature are in a "seesaw effect" and it is difficult to obtain a higher yield. The present invention provides a copper-based catalyst that is simple to prepare, low in cost and convenient to use. The copper nanoparticles are loaded in one step on an oxide carrier containing Zn and Zr species by a high-energy plasma sputtering method, and no subsequent calcination treatment is required, simplifying the equipment and process. During the reduction treatment process of the prepared supported copper-based catalyst, new interfacial active sites can be generated between the metal and the Zn species, which is not only conducive to the further hydrogenation conversion of the formate intermediate species, but also promotes the desorption of the methanol product, and can still maintain a high methanol selectivity at a higher temperature, while improving the CO2 conversion rate, significantly improving the methanol yield, and laying the foundation for subsequent further conversion into high-value chemicals.

[0006] The object of the present invention is achieved by the following methods:

[0007] The invention provides a method for preparing a supported copper-based catalyst. The method uses copper as a main active component and an oxide containing zinc and zirconium components as a carrier. A high-energy plasma sputtering method is adopted to load copper nanoparticles on the oxide carrier, and a reduction treatment is performed to form a strong interaction between the copper metal and the zinc species in the carrier, so as to obtain a supported copper-zinc active interface-adjustable supported copper-based catalyst.

[0008] Based on the above technical solution, further, the mass fraction of the copper component in the supported copper-based catalyst is 1-30%, preferably 5-20%; the molar content of zinc in the carrier is 1-90%, preferably 10-50%, and the rest is zirconium component.

[0009] Based on the above technical solution, further, the oxide carrier containing zinc and zirconium components is prepared by any one of the following methods: co-precipitation method, deposition precipitation method, sol-gel method and flame spraying method.

[0010] Based on the above technical solution, further, the preparation method comprises the following steps:

[0011] (1) A drum-type sputtering device is used to prepare the catalyst. The drum is a cylinder with a cylindrical cavity inside. The diameter of the cylindrical cavity is 20-80 cm, preferably 30-50 cm. The drum is placed in the sputtering device with its axis parallel to the horizontal plane. The carrier powder is placed at the bottom of the drum. The sputtering target head is placed directly above the carrier powder inside the drum. The metal copper target is installed so that its surface faces downward and directly faces the carrier powder. The drum is sealed in the sputtering device cavity.

[0012] (2) Evacuate the sputtering chamber to a pressure of 8.0*10 -4 Pa, Ar gas or a mixed gas containing Ar gas is introduced into the drum, wherein the volume percentage concentration of Ar gas is 50-100%, the flow rate is 5-50ml / min, and the pressure in the drum is maintained at 0.1-1.0Pa;

[0013] (3) The plasma generator sputtering power is adjusted to 100-450W, the drum speed is increased to 1-20rpm, Ar ions bombard the copper target, and the generated nano-metal copper particles are uniformly deposited on the carrier surface; the sputtering time is 10-360min;

[0014] (4) After the sputtering is completed, a mixture of O2 and Ar gas is introduced into the cylinder until the pressure reaches normal pressure, and the volume percentage concentration of O2 in the mixture is 0.5-5%. The sputtering instrument is turned on and the catalyst powder is collected;

[0015] (5) placing the catalyst powder collected in step (4) in a hydrogen atmosphere and reducing it at a temperature of 200-600° C. and a pressure of 0.1-2 MPa for 0.5-5 h to obtain the catalyst.

[0016] Based on the above technical solution, further, the particle size of the carrier powder described in step (1) is 0.01-1000 μm, preferably 0.5-200 μm; the filling amount of the carrier powder inside the drum is 0.01-20% of the internal volume of the drum, preferably 0.1-5%.

[0017] Based on the above technical solution, further, in step (2), the vacuum is evacuated to a pressure of 9.9*10 -6 -9.0*10 - 4 Pa, the volume percentage concentration of Ar gas is 80-100%, the remaining gas is He, the flow rate is 10-30ml / min, and the pressure in the cylinder is maintained at 0.2-0.7Pa.

[0018] Based on the above technical solution, further, the mass purity of the copper target material described in step (3) is above 98%, preferably above 99.9%; the drum speed is increased to 5-10rpm, and the sputtering time is 15-240min.

[0019] Based on the above technical solution, further, in step (4), the volume percentage concentration of O2 in the mixed gas is 1-3%.

[0020] Based on the above technical solution, further, in step (5), the reduction temperature is 300-500° C. and the pressure is 0.1-0.5 MPa.

[0021] The present invention also provides a supported copper-based catalyst prepared by the preparation method.

[0022] The present invention also provides the use of the above-mentioned supported copper-based catalyst, which is used in the reaction of preparing methanol by hydrogenating CO2.

[0023] Based on the above technical scheme, further, the CO2 hydrogenation reaction conditions are: the molar ratio of H2 and CO2 is 1-10, preferably 2-5, the reaction temperature is 260-360°C, preferably 280-320°C, and the reaction pressure is 0.1-10.0MPa, preferably 0.1-5MPa.

[0024] The beneficial effects of the present invention compared with the prior art are as follows:

[0025] The supported copper-based catalyst of the present invention can be prepared by a high-energy plasma sputtering method in one step. During the reduction treatment process, the prepared supported copper-based catalyst utilizes the strong metal-carrier interaction to form an active interface between the metal and the Zn component in the carrier, which is beneficial to the activation of hydrogen and further promotes the hydrogenation conversion of the formate intermediate species on the one hand, and can promote the desorption of the methanol product on the other hand. While improving the CO2 conversion rate, it can still maintain a high methanol selectivity. Compared with the commercially used Cu / ZnO / Al2O3 catalyst, under the reaction condition of 300°C, the methanol selectivity is increased from 9% to 85%, and the space-time yield of methanol is increased by 2.6 times. The present invention is conducive to opening up a new field of synthesizing methanol with copper-based catalysts at a higher reaction temperature. On the one hand, it solves the problem that methane or carbon monoxide byproducts are easily generated on noble metal catalysts or oxide catalysts, and on the other hand, it breaks through the seesaw limitation that CO2 conversion rate and methanol selectivity cannot be achieved at the same time, and has excellent application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0027] Figure 1 The catalytic performance of SP-Cu / ZnZr catalysts with different Cu contents in CO2 hydrogenation to methanol.

[0028] Figure 2 The catalytic performance of SP-Cu / ZnZr catalysts with different Zn and Zr ratios in CO2 hydrogenation to methanol.

[0029] Figure 3 The catalytic performance of CO2 hydrogenation to methanol on SP-Cu / ZnZr catalyst after treatment at different reduction temperatures.

[0030] Figure 4 The electron microscope image (A) and the Zn element energy loss spectrum (B) of the Cu catalyst after reduction in Example 8.

[0031] Figure 5 To compare the performance of CO2 hydrogenation to methanol using different preparation methods and catalysts with different compositions. DETAILED DESCRIPTION

[0032] The technical details of the present invention are described in detail by the following examples. It should be noted that the examples are only used to further illustrate the technical features of the present invention, rather than to limit the present invention.

[0033] In the present invention, CO2 conversion rate refers to the molar percentage of CO2 consumption at the reactor outlet to the amount of CO2 at the reactor inlet, wherein the CO2 consumption at the reactor outlet is the difference between the amount of CO2 at the reactor inlet and the amount of CO2 at the reactor outlet.

[0034] In the present invention, the selectivity of methanol refers to the molar percentage of methanol in all carbon-containing products (including methanol and carbon monoxide) in the product.

[0035] Example 1

[0036] The catalyst was prepared by a drum-type sputtering device. The drum was a cylinder with a cylindrical cavity inside. The diameter of the cylindrical cavity was 35 cm. The drum was placed in a sputtering device with its axis parallel to the horizontal plane. The sputtering target head was placed just above (top) the inside of the drum. The drum was sealed in the sputtering device cavity. 3 g of ZnZrO2 (molar ratio Zn:Zr=1:1) composite oxide carrier powder prepared by flame spraying (see Comparative Example 1 for the specific process) was mixed with 15 g of quartz sand particles (20-40 mesh). The mixture was then placed in a tray just below the drum. A copper target (purity of 99.9%) was installed so that its surface was facing downward to the carrier powder. The drum was evacuated to a pressure of 9.9*10 -4 Pa, high-purity Ar gas is introduced into the drum at a flow rate of 20ml / min, the pressure in the drum is maintained at 0.5Pa, the power of the Ar ion generator is adjusted to 300W, and the drum speed is increased to 5.0rpm, so that the nano-metal copper particles produced by Ar ion bombardment of the copper target are uniformly deposited on the surface of the carrier, and the sputtering time is 10 minutes; after the sputtering is completed, a 1% volume content O2 / Ar mixed gas is introduced into the drum to passivate the catalyst, and the passivation gas is turned off after 30 minutes, and Ar gas is introduced until the pressure reaches normal pressure. The inner cavity of the sputtering instrument is opened to collect the catalyst powder. After testing, the mass loading of Cu is 4.9%, and the average particle size of Cu particles is 3.1nm, which is recorded as SP-Cu / ZnZr-1.

[0037] The catalyst evaluation experiment was conducted in a fixed bed microreactor. The reactor was a stainless steel reactor lined with a quartz tube. The catalyst was first reduced with pure hydrogen at atmospheric pressure and 400°C for 1 hour in the reactor, and then switched to a mixture of CO2 and H2 (volume ratio CO2:H2=1:3) at 3.0MPa and 4800ml / (g cat. h) mass space velocity, the reaction was carried out at 260, 280, 300, 320 and 340°C respectively. The product after 1 hour of reaction was monitored online by gas chromatography. The reaction results are shown in Figure 1 .

[0038] Example 2

[0039] The catalyst preparation and evaluation process were the same as in Example 1, except that the sputtering time was increased to 15 minutes. After testing, the mass loading of Cu was 9.5%, and the average particle size of Cu particles was 2.5 nm, which was recorded as SP-Cu / ZnZr-2. The reaction results are shown in Figure 1 .

[0040] Example 3

[0041] The catalyst preparation and evaluation process were the same as in Example 1, except that the sputtering time was increased to 30 minutes. After testing, the mass loading of Cu was 22.0%, and the average particle size of Cu particles was 2.5 nm, which was recorded as SP-Cu / ZnZr-3. The reaction results are shown in Figure 1 .

[0042] Depend on Figure 1 It can be seen that different Cu contents (5-20%) have little effect on CO2 conversion, and there is no corresponding relationship between CO2 conversion and Cu content. In addition, when the Cu content is less than 10%, it has little effect on methanol selectivity, but a higher Cu content (about 20%) leads to a significant decrease in methanol selectivity.

[0043] Example 4

[0044] The catalyst preparation process is the same as that of Example 2, except that the molar ratio of Zn to Zr in the ZnZrO2 composite oxide carrier prepared by flame spraying is Zn:Zr=1:3, denoted as SP-Cu / ZnZr-4, and the reaction results are shown in Table 1. The reactor is loaded with 0.25g of the SP-Cu / ZnZr-4 catalyst prepared in Example 4, and subjected to reduction treatment at 400°C for 1 hour in a pure hydrogen atmosphere at a pressure of 0.1MPa; a mixed gas of the reaction raw materials CO2 and H2 (volume ratio CO2:H2=1:3) is introduced, and the reaction is carried out at a pressure of 3.0MPa and a mass space velocity of 4800ml / (g cat h) were reacted at 260, 280, 300, 320, 340, and 360°C for 1 hour. Figure 2 .

[0045] Example 5

[0046] The catalyst preparation process and evaluation process are the same as in Example 4, except that the molar ratio of Zn to Zr in the ZnZrO2 composite oxide carrier prepared by flame spraying is Zn:Zr=1:2, denoted as SP-Cu / ZnZr-5, and the reaction results are shown in Figure 2 .

[0047] Depend on Figure 2 It can be seen that adjusting the molar ratio of Zn and Zr in the carrier can significantly change the catalytic performance. When the ratio of Zn to Zr is 1:3 and 1:2, the methanol yield reaches the maximum at a reaction temperature of 280 degrees; when the ratio of Zn to Zr is 1:1, the methanol yield reaches the maximum at a reaction temperature of 300 degrees.

[0048] Example 6

[0049] The reactor was loaded with 0.25 g of the SP-Cu / ZnZr-2 catalyst prepared in Example 2 and subjected to reduction treatment at 200° C. for 1 hour in a pure hydrogen atmosphere at a pressure of 0.1 MPa; a mixture of the reaction raw materials CO2 and H2 (volume ratio CO2:H2=1:3) was introduced at a pressure of 3.0 MPa and a mass space velocity of 4800 ml / (g cat h), the reaction was carried out at 260, 280, 300, 320 and 340 °C for 1 hour respectively. Figure 3 .

[0050] Example 7

[0051] The catalyst evaluation process was the same as in Example 6, with the reduction treatment temperature being 300°C. Figure 3 .

[0052] Example 8

[0053] The catalyst evaluation process was the same as in Example 6, with the reduction treatment temperature being 400°C. Figure 3 The electron microscope photos and elemental analysis of the reduced catalyst are shown in Figure 4 .

[0054] Depend on Figure 4 The electron microscope photograph shows that the Cu particles are loaded on the carrier, and there is an amorphous coating layer on the surface of the Cu particles. From the elemental analysis of the energy loss spectrum, it can be seen that compared with the area without sample (area II), a signal of Zn is found in the coating layer (area I), indicating that the area is a Zn species, confirming that the method of the present invention can utilize the strong metal-carrier interaction to induce the formation of a Cu-Zn interface on the surface of the supported Cu catalyst.

[0055] Example 9

[0056] The catalyst evaluation process was the same as in Example 6, with the reduction treatment temperature being 500°C. Figure 3 .

[0057] Depend on Figure 3 It can be seen that the methanol yield first increases and then decreases as the reaction temperature increases, reaching a maximum value at 300 degrees, and the reduction temperature significantly affects the catalyst performance. When the reduction temperature is 400 degrees, the methanol yield reaches a maximum value.

[0058] Comparative Example 1

[0059] Preparation of zinc zirconium oxide catalyst with Zn:Zr=1:1 (molar ratio) by flame spraying method: 21.31g of zinc 2-ethylhexanoate was weighed and dissolved in 135ml of xylene, 29.18g of zirconium acetylacetonate was weighed and dissolved in 100ml of 2-ethylhexanoic acid solvent, the above solutions were mixed and ultrasonically treated for 1 hour. The prepared solution was then pumped into the flame spray device at a flow rate of 5ml / min, and the catalyst powder was collected on filter paper after the experiment, which was recorded as ZnZrO2. 0.25g of ZnZrO2 catalyst prepared in Comparative Example 1 was loaded into the reactor and reduced at 400°C for 1 hour in a pure hydrogen atmosphere at a pressure of 0.1MPa; a mixed gas of the reaction raw materials CO2 and H2 (volume ratio CO2:H2=1:3) was introduced, and the reaction was carried out at a pressure of 3.0MPa and a mass space velocity of 4800ml / (g cat h) at 300 °C for 1 hour. Figure 5 .

[0060] Comparative Example 2

[0061] Preparation of Cu / ZnZr catalyst by flame spraying in one step: Weigh 2.42g of copper acetate monohydrate powder and dissolve it in a mixture of 50ml methanol and 50ml xylene, weigh 25.89g of zirconium n-butoxide and dissolve it in 40ml xylene, weigh 19.62g of zinc 2-ethylhexanoate and dissolve it in 100ml xylene, mix the three solutions and ultrasonically treat them for 1 hour. Then pump the prepared solution into the flame spraying device at a flow rate of 5ml / min, collect the catalyst powder on the filter paper after the experiment, and record it as CuZnZr. The catalyst evaluation process is the same as that of Comparative Example 1, and the results are shown in Figure 5 .

[0062] Comparative Example 3

[0063] The reactor was loaded with 0.25 g of commercial CuZnAl catalyst (produced by Yalian Company) and reduced in a pure hydrogen atmosphere at 400 ° C for 1 hour at a pressure of 0.1 MPa. A mixed gas of the reaction raw materials CO2 and H2 (volume ratio CO2:H2=1:3) was introduced at a pressure of 3.0 MPa and a mass space velocity of 4800 ml / (g cat h) at 300 °C for 1 hour. Figure 5 .

[0064] Depend on Figure 5It can be seen that compared with the ZnZr oxide catalyst without Cu in Comparative Example 1, the methanol selectivity of the SP-Cu / ZnZr catalyst is equivalent, but the conversion rate is higher, and the methanol yield is increased by 2.6 times. Compared with the Cu / ZnZr catalyst prepared by flame spraying in one step in Comparative Example 2, the methanol selectivity of the SP-Cu / ZnZr catalyst is increased by 10 times. Although the CO2 conversion rate on the catalyst in Comparative Example 2 is higher, the methanol yield cannot be increased due to the limitation of selectivity. Compared with the commercial CuZnAl catalyst in Comparative Example 3, the methanol yield in Comparative Example 3 is also limited by the selectivity and cannot be increased. In summary, the SP-Cu / ZnZr catalyst of the present invention has a higher methanol selectivity and conversion rate, and obtains a higher methanol yield.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a supported copper-based catalyst, characterized in that: With copper as the main active component and oxide containing zinc and zirconium components as the carrier, copper nanoparticles are loaded on the oxide carrier by high-energy plasma sputtering, and then reduced to form a strong interaction between copper metal and zinc species in the carrier, thus obtaining a loaded copper-based catalyst with an adjustable copper-zinc active interface.

2. The preparation method according to claim 1, characterized in that: The mass fraction of the copper component in the supported copper-based catalyst is 1-30%, preferably 5-20%; the molar content of zinc in the carrier is 1-90%, preferably 10-50%, and the rest is zirconium component.

3. The preparation method according to claim 1, characterized in that: The oxide support containing zinc and zirconium components is prepared by any one of a coprecipitation method, a deposition precipitation method, a sol-gel method and a flame spray method.

4. The preparation method according to any one of claims 1 to 3, characterized in that The preparation method comprises the following steps: (1) A drum-type sputtering device is used to prepare the catalyst. The drum is a cylinder with a cylindrical cavity inside. The diameter of the cylindrical cavity is 20-80 cm, preferably 30-50 cm. The drum is placed in the sputtering device with its axis parallel to the horizontal plane. The carrier powder is placed at the bottom of the drum. The sputtering target head is placed directly above the carrier powder inside the drum. The metal copper target is installed so that its surface faces downward and directly faces the carrier powder. The drum is sealed in the sputtering device cavity. (2) Evacuate the sputtering chamber to a pressure of 8.0*10 -4 Pa, Ar gas or a mixed gas containing Ar gas is introduced into the drum, wherein the volume percentage concentration of Ar gas is 50-100%, the flow rate is 5-50ml / min, and the pressure in the drum is maintained at 0.1-1.0Pa; (3) The plasma generator sputtering power is adjusted to 100-450W, the drum speed is increased to 1-20rpm, Ar ions bombard the copper target, and the generated nano-metal copper particles are uniformly deposited on the carrier surface; the sputtering time is 10-360min; (4) After the sputtering is completed, a mixture of O2 and Ar gas is introduced into the cylinder until the pressure reaches normal pressure, and the volume percentage concentration of O2 in the mixture is 0.5-5%. The sputtering instrument is turned on and the catalyst powder is collected; (5) placing the catalyst powder collected in step (4) in a hydrogen atmosphere and reducing it at a temperature of 200-600° C. and a pressure of 0.1-2 MPa for 0.5-5 h to obtain the catalyst.

5. The preparation method according to claim 4, characterized in that: The particle size of the carrier powder in step (1) is 0.01-1000 μm, preferably 0.5-200 μm; the amount of the carrier powder in the drum is 0.01-20% of the internal volume of the drum, preferably 0.1-5%; in step (2), the vacuum is evacuated to a pressure of 9.9*10 -6 -9.0*10 -4 Pa, the volume percentage concentration of Ar gas is 80-100%, the remaining gas is He, the flow rate is 10-30ml / min, and the pressure in the cylinder is maintained at 0.2-0.7Pa.

6. The preparation method according to claim 4, characterized in that: The mass purity of the copper target described in step (3) is above 98%, preferably above 99.9%; the drum speed is increased to 5-10rpm, and the sputtering time is 15-240min; the volume percentage concentration of O2 in the mixed gas in step (4) is 1-3%.

7. The preparation method according to claim 4, characterized in that: In step (5), the reduction temperature is 300-500° C. and the pressure is 0.1-0.5 MPa.

8. A supported copper-based catalyst obtained by the preparation method according to any one of claims 1 to 7.

9. The use of the supported copper-based catalyst according to claim 8, characterized in that: It is used in the reaction of producing methanol by hydrogenation of CO2.

10. The use according to claim 9, characterized in that: The CO2 hydrogenation reaction conditions are: the molar ratio of H2 to CO2 is 1-10, preferably 2-5, the reaction temperature is 260-360°C, preferably 280-320°C, and the reaction pressure is 0.1-10.0MPa, preferably 0.1-5MPa.

Citation Information

Patent Citations

  • Copper-based hydrogenation catalyst prepared by flame jet cracking method and preparation and application thereof

    CN108144610A

  • Copper-based catalyst for preparing methyl glycolate and preparation and application thereof

    CN110871071A

  • High-temperature-resistant and anti-sintering supported copper nano-catalyst as well as preparation and application thereof

    CN115430424A

  • Supported copper-based nano catalyst as well as preparation method and application thereof

    CN115707517A

  • Catalyst for preparing low-carbon alkane as well as preparation and application of catalyst

    CN116474778A

Cited By

  • Preparation method and application of catalyst for preparing methanol through hydrogenation of carbon dioxide

    CN121911460A